How policies affect women's economic position within the family: Labor market institutions and wives' contribution to household income - Margarita Estévez-Abe; Tanja Hethey (Luxembourg Income Study (LIS), 2008)
This paper examines the effects of public policies in shaping wives' economic standing within the family in advanced industrial societies. It conducts two types of statistical analysis. One is a multi-level regression analysis to examine the effects of employment protection regulation, the size of the public sector, tax policy, and mother-friendly social policy while controlling for individual attributes of wives (age and education) as well as household characteristics (husband's income, presence of children, and the relative educational background between the spouses). The other consists of a two-step regression analysis, whereby coefficients on personal attributes are first measured country by country, then compared across countries. Both analyses use the micro-level data from the Luxembourg Income Study for 16 advanced industrial societies. It finds that strong employment protection negatively affects women's capacity to attain economic parity vis-à-vis their husbands by reducing women's employment levels, while the size of the public sector positively affects wives' contribution to household income by improving women's wages. The positive effect of the public sector is independent of mother-friendly social policies.
Keywords: 330; Weibliche Arbeitskräfte; Haushaltseinkommen; Frauenpolitik; Arbeitsmarkt; Institutionalismus; OECD-Staaten